With spray, paint ‘The She!’: A Semiotic Panel to Graffiti on Iraqi Women in Tahrir Square, Baghdad (October 25th, 2019) - Taher, Shamal; Halawachy, Huda (Journal of Ecohumanism, 2024)
This study seeks to identify and analyse the semiotic elements in graffiti on Iraqi women displayed on the walls of Baghdad’s Tahrir Square during the October 25th, 2019 demonstration. Utilizing a qualitative approach, the researchers gathered 19 samples of graffiti created by anonymous Iraqi artists through various internet sources. Adopting Peirce’s Semiotic Triangle Model, the study unveiled that Iraqi women’s graffiti in Tahrir Square was interpreted to articulate peaceful messages about Iraqi women. Upon analyzing the data, the findings further uncovered intriguing insights, showcasing women’s diverse figures and contributions in the sense that:(3) graffiti as a figure of liberty and peace, (6) graffiti as a figure of human rights activism, (1) graffiti as a figure of steadfast prayer, (2) graffiti as a figure of love and devotion to Iraq, (3) graffiti as a figure of protest, (2) graffiti as a figure of suffering due to sectarianism, and (2) graffiti as a figure of Iraq. The findings concluded that semiotic elements go hand in hand with the corresponding graffiti inscriptions (whether in Arabic or English) in encrypting Iraqi women’s figures.